2017
DOI: 10.1016/j.jcf.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between multiple-breath nitrogen washout systems in children and adults

Abstract: Agreement of MBW outcomes between setups is poor and explained by nitrogen measurement techniques and breathing pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 42 publications
7
49
2
Order By: Relevance
“…All washout indices reported here were adjusted for resting lung volume (FRC) and the Sn III indices for VT as recommended. Comparison to other studies currently seems constrained by different equipment setups . For example, in the study by Verbanck et al LCI 2.5% was abnormal in 78% patients with severe lung disease while LCI 2.5% was abnormal in 87% of patients with CF in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…All washout indices reported here were adjusted for resting lung volume (FRC) and the Sn III indices for VT as recommended. Comparison to other studies currently seems constrained by different equipment setups . For example, in the study by Verbanck et al LCI 2.5% was abnormal in 78% patients with severe lung disease while LCI 2.5% was abnormal in 87% of patients with CF in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Several studies have shown that MBW results are device and tracer gas specific . In this study, the tracer gas and a substantial part of the hardware are common for the devices, both based on the ultrasonic flowmeter.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that MBW results are device and tracer gas specific. 27,28 In this study, the tracer gas and a substantial part of the hardware are common for the devices, both based on the ultrasonic flowmeter. Apart from the difference in signal acquisition (main-stream vs side-stream), we present differences in the analysis algorithms that explain to a large extent the FRC differences between the setups.…”
Section: Physiological Aspectsmentioning
confidence: 99%
“…While international recommendations exist for best practice for both tests [53,87], issues remain regarding standardisation across centres. There are known differences between equipment, software algorithms and protocols that limit comparability and thus clinical utility, for both FOT [88,89] and MBNW [90][91][92]. This lack of comparability has also impacted the availability of reliable and/or widely applicable reference values from a healthy population to derive predicted equations.…”
Section: Current Limitations and Open Questionsmentioning
confidence: 99%